Livability Measures As Standard, Norms And Procedures Of Planning Process For Indonesian Cities - Bernardus Djonoputro (Jurnal Syntax Transformation, 2020)
This article examines the adoption of livability at a conceptual level into the Indonesian national planning practice as the country is facing the height of urbanization. Connection between the two is examined through the analysis of theories of livability, state of urbanization and livability of Indonesian cities, and existing norms, standards and procedure in planning for Indonesian cities. The paper intends to introduce the need of adopting the concept of livability into the planning due process expected to systematically eliminate vested interests, political clout and subjectivity, which in turn will make livability itself as tool to measure well-being of a city.